2021
DOI: 10.1177/00220345211000656
|View full text |Cite
|
Sign up to set email alerts
|

Filifactor alocis: Recent Insights and Advances

Abstract: Filifactor alocis, a fastidious Gram-positive obligate anaerobic bacterium, is a newly appreciated member of the periodontal community that is now proposed to be a diagnostic indicator of periodontal disease. Its pathogenic characteristics are highlighted by its ability to survive in the oxidative stress–rich environment of the periodontal pocket and to significantly alter the microbial community dynamics by forming biofilms and interacting with several oral bacteria. Here, we describe the current understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 61 publications
2
35
0
Order By: Relevance
“…In recent studies, F . alocis has been proposed to be included within the red complex of periodontal pathogens [ 48 ], probably due to these properties that enable this bacterium to colonize, survive, and outcompete other bacteria within the inflammatory environment of the periodontal pocket [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, F . alocis has been proposed to be included within the red complex of periodontal pathogens [ 48 ], probably due to these properties that enable this bacterium to colonize, survive, and outcompete other bacteria within the inflammatory environment of the periodontal pocket [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…F. alocis has recently been proposed to be a pathogen and diagnostic of periodontal disease (Aja et al, 2021), and was found at significantly higher level in periodontal patients (Lee et al, 2020;Spooner et al, 2016). It is a Gram-positive anaerobe that resists oxidative stress, interacting with gingival epithelial cells and forming biofilms in the periodontal pocket (Moffatt et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that increased diversity might trigger a pro-inflammatory response and decrease mucosal clearance in adenoids, leading to hypertrophy and obstruction of the airways. We also found interesting correlations between Th17 and several bacterial in the oropharynx; Th17 were inverse correlated with Filifactor , a gram-positive genus of bacteria comprising F. alocis , which has recently been identified as a biomarker of periodontal disease ( Aja et al, 2021 ) and in tonsillar cancer patients ( De Martin et al, 2021 ), with Treponema , also a genus of bacteria causative of periodontitis ( T. denticola ). Again, these results suggest that bacteria in caries might translocate to and colonize other sites within the oral cavity, and trigger a pro-inflammatory response and decrease mucosal clearance in tonsils, leading to infection (tonsillitis).…”
Section: Discussionmentioning
confidence: 65%